Evaluation of Heavy Metal Pollution (Lead, Cadmium, Copper) in Some Areas of the Tigris River in Baghdad Governorate - Dr. Salwa Hashim Khalaf Al Shamary; Prof. Dr. Hamid Hussain Rijab Al-Joubory (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study was conducted to assess the possible state of contamination in the waters of the Tigris River and the soil of the beaches adjacent to it with some heavy elements as a result of the direct release of sewage water and industrial wastes of all kinds therein without resorting to treating them with modern scientific methods and its impact on increasing the problem of environmental pollution. Three soil and water sampling sites were selected, the first located under Al-Jumhuriya Bridge, the second located under Bab Al-Muadham Bridge, and the third under Al-Ahrar Bridge in the center of Baghdad Governorate, with three replicates for each sample. However, extraction of heavy metal ions (Cd2+, pb2+, Fe2+, Cu2+, Mn2+) was carried out using the chelating agent Diethylene triamine penta acetic acid (DTPA). The models were measured with an atomic absorption device, and the following pollution indices were used: enrichment factor (EF), contamination factor (CF), Index of Geochemical Load (lgeo), and Pollution load index (PLI). That can give a clear and correct assessment of the degree of pollution occurring as a result of various human activities, which has directly contributed to the pollution of the waters of the Tigris River and the surrounding soil. The results showed a significant increase in the values of (EF) for the lead element in the soil adjacent to the Ahrar Bridge, reaching 32.25. While the copper element recorded a slight increase in the percentage of (EF), reaching 4.78 in the same location. However, the (CF) recorded a significant increase in the values for the two elements lead and copper for all sites, with a clear increase in the lead values in the soil adjacent to the Ahrar Bridge, reaching 98.97 and 15.54 for the two elements, respectively. These percentages are considered an extremely dangerous indicator of the presence of a very high state of pollution. The highest value of the (PLI) was shown in the soil adjacent to the Ahrar Bridge, followed by the Bab al-Muadham Bridge soil, then the Jumhouriya Bridge soil. The lgeo index also showed a variation in values from one place to another. The highest value of lead appeared in the soil adjacent to the Ahrar Bridge, reaching 7.00. It is classified as extremely contaminated and dangerous to public health. Moreover, water tests showed the presence of high concentrations of lead, reaching (294.2, 300.7, 292.5) mg/L in the course of the Tigris River under the Al-Jumhuriya Bridge, Bab Al-Muadham and Al-Ahrar, respectively, are naturally considerably higher based on international standards adopted to measure the extent of water contamination by heavy elements. This increase may be attributed to the continuous release of sewage water and factory waste into the river stream without proper treatment.